Metadata and Location-Based Digital Document Authenticity Identification - Al Farizi, Teuku Ahmad Hafiz; Tanjung, Mahardika Abdi Prawira (Marqcha Institute, 2026)
The growth of digital documents has simplified the creation, storage, and distribution of information, but it has also increased the possibility of document forgery and manipulation. This study implements a digital forensic approach to support the identification of digital document authenticity through metadata and location analysis. The research method follows the National Institute of Standards and Technology (NIST) framework, consisting of collection, examination, analysis, and reporting. The system was developed as a web-based application using HTML, CSS, and JavaScript, with support for JPG, PNG, PDF, and DOCX files. The analyzed metadata includes file type, file size, creation time, modification time, software or device information, author identity, and GPS coordinates when available. The system was tested using black box testing on key features, including file upload, fetch URL, export JSON, clear, and GPS location display. The results show that the system is able to extract and present metadata in a structured manner and support the initial verification of digital document authenticity. Metadata can be used as an early indicator to detect inconsistencies in document history, although the reliability of the analysis depends on the completeness of metadata stored in the examined file.